Thermodynamic investigation of the interaction between the [(η6-p-cymene)Ru(benzaldehyde-N4-phenylthiosemicarbazone)Cl]Cl anticancer drug and ctDNA: multispectroscopic and electrochemical studies1. Issue 53 (11th June 2015) - Huang, Shan; Zhu, Fawei; Xiao, Qi; Liang, Yu; Zhou, Quan; Su, Wei
<x xml:space="preserve">Abstract</x> The interaction between the [(η6-p-cymene)Ru(benzaldehyde-N4-phenylthiosemicarbazone)Cl]Cl anticancer drug and ctDNA was systematically investigated by multispectroscopic and electrochemical studies.